Bowel preparation prior to colonoscopy with a new colonic irrigation device: Results of a prospective observational study - Teich, Niels; Klecker, Chris; Klugmann, Tobias; Dietel, Peter (Endoscopy International Open, 2022)
Background and study aims The success of colonoscopy is mainly dependent on the effectiveness of prior bowel preparation (BP). Patients often consider BP to be the most burdensome part of colonoscopy, which might be a main barrier to the procedure. The aim of this study was to evaluate safety and effectiveness of colonic irrigation with a new colon hydrotherapy (CHT) device as an alternative to traditional oral BP. Patients and methods A prospective, non-randomized observational study was conducted to evaluate the quality of BP. A BP was considered effective if a score of 6 or better through the Boston Bowel Preparation Scale (BBPS) could be reached. Colonoscopy was performed immediately following colonic irrigation. For safety analysis, data on adverse events (AEs) were collected. Among the secondary outcomes, the BBPS assessed in each bowel segment and cecal intubation rate were analyzed. Results Twenty-eight consecutive patients (11 male [39.3%] and 17 [60.7 %] female) undergoing screening/surveillance or diagnostic colonoscopy were enrolled. Mean age was 54 ± 12.4 years (range 19–80). The evaluated mean BBPS was 7.8 ± 1.5. Twenty-five patients (89.3 %) had a BBPS score of 6 or above. Colonic irrigation was performed without any complications and no AEs were reported within 30 days. The cecal intubation rate was 100 %.Conclusions Colonic irrigation with a new CHT device is an effective and low-risk alternative to traditional oral preparation prior to colonoscopy.